Conservative non‐surgical management in medication related osteonecrosis of the jaw: A retrospective study. Issue 5 (2nd July 2020) - Albanese, Massimo; Zotti, Francesca; Capocasale, Giorgia; Bonetti, Stefano; Lonardi, Fabio; Nocini, Pier Francesco
Abstract: Objectives: To date, the best treatment for Medication Related Osteonecrosis of the jaw (MRONJ) is controversial. Recent studies suggest different therapies, considering the stage of MRONJ; however, sometimes patients, although with remarkable extension of disease, cannot undergo surgery. The purpose of present preliminary study was to evaluate the efficacy of conservative non‐surgical treatment of MRONJ lesions in a cohort of patients ineligible for surgery or refusing any surgical treatment for stage II and III of MRONJ. Materials and methods: Patients with MRONJ (staging II or III) ineligible for surgical treatment were selected for a retrospective study. A conservative non‐surgical therapy (antibiotics and antiseptic) was administered for 1 year. Five scheduled checks were performed to assess changes in signs and symptoms during the observational period. Results: Our observation was carried out on 12 patients. Improvement of signs and symptoms of disease were observed in population. Conclusion: This study suggests that non‐surgical treatment may be a valid therapeutic option in patients ineligible for surgery. The sample size is small, further studies should be carried out to satisfy the aim of a conservative non‐surgical treatment protocol establishment.